A systematic review of the effectiveness and roles of advanced practice nursing in older people - Morilla-Herrera, Juan Carlos; García-Mayor, Silvia; Martín-Santos, Francisco Javier; Kaknani-Uttumchandani, Shakira; León-Campos, Álvaro; Caro-Bautista, Jorge; Morales-Asencio, José Miguel (Elsevier, 2015)
Objectives: To identify, assess and summarize available scientific evidence about the effect of interventions deployed by advanced practice nurses when providing care to older people in different care settings, and to describe the roles and components of the interventions developed by these professionals. Background: In older people, evidence of advanced practice roles remains dispersed along different contexts, approaches and settings; there is little synthesis of evidence, and it is not easy to visualize the different practice models, their components, and their impact. Design: Systematic review. Data sources: Sixteen electronic databases were consulted (1990–2014). The research also included screening of original studies in reviews and reports from Centers of Health Services Research and Health Technology Agencies. Review methods: Studies were assessed by two reviewers with the Cochrane risk of bias tool. They were classified depending on the type of follow-up (long and short-term care) and the scope of the service (advanced practice nurses interventions focused on multimorbid patients, or focused on a specific disease). Results: Fifteen studies were included. In long-term settings, integrative, multi-component and continuous advanced practice nursing care, reduced readmissions, and increased patients’ and caregivers’ satisfaction. Advanced practice nurses were integrated within multidisciplinary teams and the main interventions deployed were patient education, multidimensional assessments and coordination of multiple providers. Conclusion: Positive results have been found in older people in long-term care settings, although it is difficult to discern the specific effect attributable to them because they are inserted in multidisciplinary teams. Further investigations are needed to evaluate the cost-effectiveness of the two modalities detected and to compare internationally the interventions developed by advanced practice nurses.
Keywords: Estudiantes de enfermería - Competencias y funciones; Advanced practice nursing; geriatric nursing; health services for the older; professional role and systematic review; nursing interventions